Age-related and stand-wise estimates of carbon stocks and sequestration in the aboveground coarse wood biomass of wetland forests in the northern Pantanal, Brazil - Schöngart, Jochen; Arieira, Julia; Felfili Fortes, C.; Cezarine de Arruda, E.; Nunes da Cunha, C. (Biogeosciences, 2011)
In this study we use allometric models combined with tree ring analysis to estimate carbon stocks and sequestration in the aboveground coarse wood biomass (AGWB) of wetland forests in the Pantanal, located in central South America. In four 1-ha plots in stands characterized by the pioneer tree species Vochysia divergens Pohl (Vochysiaceae) forest inventories (trees ≤10 cm diameter at breast height, D) have been performed and converted to estimates of AGWB by two allometric models using three independent parameters (D, tree height H and wood density). We perform a propagation of measurement errors to estimate uncertainties in the estimates of AGWB. Carbon stocks of AGWB vary from 7.8±1.5 to 97.2±14.4MgC ha-1 between the four stands. From models relating tree ages determined by dendrochronological techniques to C-stocks in AGWB we derived estimates for C-sequestration which differs from 0.50±0.03 to 3.34±0.31MgC ha-1 yr-1. Maps based on geostatistic techniques indicate the heterogeneous spatial distribution of tree ages and C-stocks of the four studied stands. This distribution is the result of forest dynamics due to the colonizing and retreating of V. divergens and other species associated with pluriannual wet and dry episodes in the Pantanal, respectively. Such information is essential for the management of the cultural landscape of the Pantanal wetlands. © Author(s) 2011.
Keywords: Aboveground Biomass; Age Class; Allometry; Biogeochemistry; Carbon Sequestration; Coarse Woody Debris; Colonization; Cultural Landscape; Dendrochronology; Dicotyledon; Error Analysis; Forest Inventory; Landscape Planning; Pioneer Species; Tree Ring; Uncertainty Analysis; Wetland; Pantanal; Vochysia Divergens; Vochysiaceae